Heat pumps complex for recycling of secondary energy resources of petrochemical plants - M. A. Taimarov; V. K. Ilyin; A. L. Osipov; A. N. Dolgova; A. V. Akhmerov (Известия высших учебных заведений: Проблемы энергетики)
The created heat pump complex allows to utilize simultaneously different types of secondary energy resources of petrochemical industries. The main potential for the resources used for the developed heat pump complex is the heat of flammable waste gases and heat of circulating water, and the final received energy resources are heat of heati ng water with a temperature of 150°0C and electricity for internal and external consumption.